DIETARY MANAGEMENT IN AMLAPITTA - A CLINICAL STUDY (International Journal of Ayurveda and Pharma Research, 2016)
Amlapitta is a disease of Annavaha strotas, where there is increase in Amla and Drava guna of Pitta and has resemblance with the symptoms of Non-ulcer Dyspepsia. It is one of the commonest conditions affecting the younger or middle aged people. The causative factors include improper dietary habits, spicy irritant foods, stress etc. Ayurveda agrees that no medicine is equivalent to food; it is possible to make a person, disease free merely with appropriate diet. One has to follow code of dietetics for better health. METHOD: Appropriate quantity and quality of food consumed helps to prevent and control hyperacidity, so for the present clinical trial a 20 days dietary chart was prepared for 30 patients of Amlapitta aged 18-50yrs of either gender selected from IPD and OPD of Panchakarma of Y.M.T Ayurvedic Medical College, Kharghar, Navi Mumbai. Diagnostic criteria were mainly based on the signs and symptoms of Amlapitta as per Ayurvedic literature. Pre and post therapy results were analyzed statistically for p value using t test. RESULT: The statistical analysis revealed highly significant results (p